The Effect of the Use of M-Payment, Islamic Financial Literacy, Locus of Control on the Financial Behavior - Risna Yunia Rahma; Siti Zulaikha (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Riset ini bertujuan untuk mendapatkan fakta empiris pengaruh penggunaan m- payment, literasi keuangan syariah, locus of control terhadap perilaku keuangan mahasiswa muslim Surabaya sepanjang pandemi Covid- 19. Riset ini ialah riset kuantitatif. Metode pengambilan sampel dilakukan dengan purposive sampling, kepada 119 mahasiswa muslim Surabaya yang memakai mobile payment. Metode analisis yang digunakan merupakan Structural Equation Modelling-Partial Least Square (SEM-PLS). Hasil riset ini menampilkan bahwa penggunaan m-payment mempengaruhi positif serta signifikan terhadap perilaku keuangan, literasi keuangan syariah mempengaruhi positif serta signifikan terhadap perilaku keuangan, serta economic locus of control mempengaruhi positif serta signifikan terhadap perilaku keuangan. Riset ini mempunyai implikasi bahwa literasi keuangan syariah merupakan aspek yang sangat mempengaruhi dalam menunjang perilaku keuangan seorang, dimana dengan literasi keuangan syariah yang baik diiringi keahlian dalam mengambil keputusan keuangan dapat menghasilkan industri keuangan yang sehat. Walaupun tingkat literasi keuangan syariah mahasiswa muslim Surabaya terletak pada tingkat yang baik, diharapkan pelaku industri keuangan senantiasa mengedukasi warga khususnya mahasiswa dan menyadari bahwa perilaku keuangan sangatlah penting. Riset ini terbatas pada penyebaran sampel yang tidak menyeluruh serta tidak mempertimbangkan bagaimana perilaku keuangan responden saat sebelum pandemi Covid-19 terjadi. Kata Kunci: Mobile payment, Literasi Keuangan Syariah, Locus of control, Perilaku Keuangan.   ABSTRACT This research aims to obtain empirical facts about the effect of using m-payments, Islamic financial literacy, locus of control on the financial behavior of Surabaya Muslim students during the Covid-19 pandemic. This research is quantitative research. The sampling method was carried out by purposive sampling, to 119 Muslim students in Surabaya who used mobile payments. The analytical method used is Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study show that the use of m-payment has a positive and significant effect on financial behavior, Islamic financial literacy which has a positive and significant influence on financial behavior, and economic locus of control which has a positive and significant influence on financial behavior. This research shows that Islamic financial literacy is a very influential aspect in supporting the behavior of an employee, where good Islamic financial literacy is accompanied by financial decision results that can produce a healthy financial industry. Although the level of Islamic financial literacy of Surabaya Muslim students is at a good level (well literate), it is hoped that the financial industry players will educate citizens, especially students, and realize that financial behavior is important. This research is limited to a sample distribution that is not comprehensive and does not take into account the financial behavior of respondents before the Covid-19 pandemic occurred. Keywords: Mobile payment, Islamic Financial Literacy, Locus of control, Financial behavior.   DAFTAR PUSTAKA Dew, J., & Xiao, J. (2011). The financial management behavior scale: Development and validation. Journal of Financial Counseling and Planning, 22(1), 43-59. Grable, J., Joo-yung P., & So-Hyun J. (2009). Explaining financial management behavior for Koreans living in the United States. The Journal of Consumer Affairs, 43(1), 80-107. Ida, I., & Dwinta, C. Y. (2010). Pengaruh locus of control, financial knowledge, income terhadap financial management behavior. Jurnal Bisnis dan Akuntansi, 12(3), 131-144. https://doi.org/10.34208/jba.v12i3.202 Kholilah, N. A., & Iramani. (2013). Studi financial management behavior pada masyarakat Surabaya. Journal of Business and Banking, 3(1), 69-80. http://dx.doi.org/10.14414/jbb.v3i1.255 Liu, T., Pan, B., & Yin, Z. (2020). Pandemic, mobile payment, and household consumption: Micro-evidence from China. Emerging Markets Finance and Trade, 56(10), 2378-2389. https://doi.org/10.1080/1540496X.2020.1788539 Patil, P., Tamilmani, K., Rana, N. P., & Raghavan, V. (2020). Understanding consumer adoption of mobile payment in India: extending meta-utaut model with personal innovativeness, anxiety, trust, and grievance redressal. International Journal of Information Management, 54, 1-16. https://doi.org/10.1016/j.ijinfomgt.2020.102144 Perry, V. G., & Morris, M. D. (2005). Who is in control? The role of self-perception, knowledge, and income in explaining consumer financial behavior. The Journal of Consumer Affairs, 39(2), 299-313. https://psycnet.apa.org/doi/10.1111/j.1745-6606.2005.00016.x Rahim, S. H. A., Rashid, R. A., & Hamed, A. B. (2016). Islamic financial literacy and its determinants among university students: An exploratory factor analysis. International Journal of Economic and Financial Issues, 6(S7), 32-35. Salamanca, N., de Grip, A., Fouarge, D., & Montizaan, R. (2020). Locus of control and investment in risky assets. Journal of Economic Behavior and Organization, 177, 548-568. https://doi.org/10.1016/j.jebo.2020.06.032 Sapir, A. S. M., & Ahmad, W. M. W. (2019). Financial literacy among Malaysian muslim undergraduates. Journal of Islamic Accounting and Business Research, 11(8), 1515-1529. https://doi.org/10.1108/JIABR-10-2017-0149 Sugiyono. (2017). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta. Xiao, J. J. (2008). Applying behavior theories to financial behavior. In Handbook of Consumer Finance Research, chapter 5. 10.1007/978-0-387-75734-6_5 Zulaihati, S., Susanti, S., & Widyastuti, U. (2020). Teachers’ financial literacy: Does it impact on financial behavior? Management Science Letters, 10, 653-658. http://dx.doi.org/10.5267/j.msl.2019.9.014